School Leadership From A to Z : Practical Lessons from Successful Schools and Businesses. - Ramsey, Robert D. (SAGE Publications, 2003)
Using a fresh approach to leadership, this resource blends proven traditional success secrets for school leaders with newfound strategies and unique methods from businesses and organizations outside the education community.